USE OF PARALLEL PORT AND IC 8255 AS SAFETY HOUSE - Arief Cahyono; Luyung Dinaini, SKom., MM Luyung Dinaini, SKom., MM (Jurnal Sistem Informasi, 2004)
In a series of parallel port utilization and IC 8255 as a safety house consists of threemain blocks include: Personal Computers, PPI 8255, lamp indicator.On the use of parallel port to be controlled by IC 8255 from a software program,which is software that contains the control word is sent by the CPU to the IC 8255. ineach control block receives commands from the signal read / write and "ControlWord". where the use of parallel port is used as output ports A, B and C are used asinputs are used as output, so lower PPI8255 can work on the mode 0. except on theeasiest mode, it has no signal source prokol for one or the other two modes.In 8255 LPT circuit requires power supply +5 V / 200mA. The power supply can begot from outside the circuit or by tapping the power supply +5 V from the computer.on the use of resistors in the circuit Rp3 it's useful to keep the data bus = 0. while forthe capacitor C5 and C6 serve to secure the WR and RD from the noise.